The search for a sustainable alternative to slash-and-burn agriculture in the World's rain forests: the Guama Model and its implementation. - Hands, Michael (The Royal Society, 2021)
This account describes the context, history and outcomes of a series of studies into the ecology of slash-and-burn (S-B) agriculture in the world's humid tropics. These studies, which began in the mid-1980s, identified promising lines of research and continued to field trials, in Central America, of candidate agricultural systems as possible sustainable alternatives to the practice. The only system to emerge from 7 years' comparative trial with any promise of sustainability, in this context, was the agroforestry technique known as alley-cropping; but only with trees of the genus Inga. Inga alley-cropping then underwent field trials with subsistence farming families in northern Honduras. The system was aimed at the twin objectives of achieving food security in basic grains, on minimal inputs, and of providing the means of eliminating further S-B in the region. Since then, Inga alley-cropping has become the heart of a sustainable and integrated rural livelihood model (the Guama Model) which is being implemented successfully in northern Honduras with some 300 families. These families had been attempting to subsist on a few hectares of land degraded by decades or centuries of S-B. The development of Inga alley-cropping, supplemented by rock phosphate and other mineral supplements, as a sustainable subsistence and cash crop alternative means that land previously being held in reserve for subsequent S-B operations can now be planted to permanent forms of agroforestry. Entire landscapes can be re-greened by productive agroforest vegetation. Achieving this at scale will require the investment of huge extension effort and funds. However, the environmental, social and economic returns are also huge; and they are sustainable. In this programme,we are seeing the vitality and goodwill of hundreds of families focussed on the raising, planting and management of trees in ways that feed the living organisms of the soil and, hence, feed themselves. In so cheerfully planting out their own futures, they plant and reshape the future of their own country. Replicating this at scale, as Rattan Lal outlines below, could reshape the future of this planet. In the mid-1980s, progress on sustainable alternatives to S-B, especially in rain forests, was frustrated by a lack of conclusiveness in the literature as to why soil fertility fails so rapidly post-burn; but also by a degree of contradiction on the impacts of the burn on certain plant nutrients. Hands (Hands 1988 The ecology of shifting cultivation. MSc thesis, University of Cambridge) concentrated on the role of soil phosphorus and attempted to resolve these contradictions. The Cambridge Alley-cropping Projects (1988-2002) continued this theme and threw light on the question of sustainable food production in rain forest environments.
Keywords: agroforestry; alley-cropping; humid tropics; slash-and-burn; soil phosphorus